Air‐Stable Copper‐Based P2‐Na7/9Cu2/9Fe1/9Mn2/3O2 as a New Positive Electrode Material for Sodium‐Ion Batteries. Issue 6 (4th May 2015) - Li, Yunming; Yang, Zhenzhong; Xu, Shuyin; Mu, Linqin; Gu, Lin; Hu, Yong‐Sheng; Li, Hong; Chen, Liquan
<x xml:space="preserve">Abstract</x> An air‐stable copper‐based P2‐Na7/9Cu2/9Fe1/9Mn2/3O2 is designed and synthesized by a simple solid‐state method and investigated as a positive electrode material for sodium‐ion batteries. The attractive long cycling stability is demonstrated by the capacity retention of 85% after 150 cycles at 1 C rate without phase transformation. The reversible Cu2+/Cu3+ redox couple in P2 phase oxides is proved for the first time.